Measuring the impact of wharf construction on the Antarctic benthos - Robinson, Ben J. O.; Hughes, Kevin A.; Seaton, David; Morley, Simon A. (Frontiers in Ecology and Evolution, 2024)
Shallow water Antarctic marine macroepifaunal assemblages live in one of the most naturally disturbed marine environments due to the impact of icebergs scouring the seafloor. They are, however, amongst the least anthropogenically impacted assemblages and are afforded protection under the Antarctic Treaty system. When the British Antarctic Survey’s Rothera Research Station wharf needed extending to accommodate the newly constructed UK polar research vessel, the RRS Sir David Attenborough, a Comprehensive Environmental Evaluation (CEE) was conducted to assess the impact. The macroepifaunal likely to be impacted by the construction was surveyed through ROV videos of five transects, centered on the middle of the construction zone, from 10–100 m deep. A pre-construction survey was completed in March 2017, as part of the CEE impact assessment, and a post-build survey in 2022 (delayed from 2021, and reduced in scope, due to the COVID-19 pandemic). Sedimentation rates were also measured before and during construction and were high during the second summer when the wharf pilings were being back filled with crushed rock. The measured differences between pre- and post-construction assemblages were minor and were not reflected in the overall number of taxa (operational taxonomic units – OTU), or diversity, but there were subtle shifts in species composition. The largest differences in the macroepifauna were a reduction in the number of the common urchin, Sterechinus neumayeri, and seastar, Odontaster validus, and were within expected variability. The small changes detected in the macroepifauna indicate it was minimally impacted and/or recovered in the subsequent two years, therefore during wharf construction the accompanying mitigation measures were robust.